(untitled) (Journal of Computational Mathematics, 2003)
In this paper we presented a convergence condition of parallel dynamic iteration methods for a nonlinear system of differential-algebraic equations with a periodic constraint. The convergence criterion is decided by the spectral expression of a linear operator derived from system partitions. Numerical experiments given here confirm the theoretical work of the paper.